DNA methylation and temperature stress in an Antarctic polychaete, Spiophanes tcherniai - Marsh, Adam G.; Pasqualone, Annamarie A. (Frontiers in Physiology, 2014)
Epigenetic modifications of DNA and histones are a primary mechanism by which gene expression activities may be modified in response to environmental stimuli. Here we characterize patterns of methyl-cytosine composition in the marine polychaete Spiophanes tcherniai from McMurdo Sound, Antarctica. We cultured adult worms at two temperatures, -1.5 C (ambient control) and +4 C (warm treatment), for four weeks. We observed a rapid capacity for S. tcherniai organismal respiration rates and underlying catalytic rates of citrate synthase to acclimate at +4 C and return to control levels. We profiled changes in the methylation states of CpG sites in these treatments using an NGS strategy to computationally reconstruct and quantify methylation status across the genome. In our analysis we recovered 120,000 CpG sites in assembled contigs from both treatments. Of those, we were able to align 28,000 CpG sites in common between the two sample groups. In comparing these aligned sites between treatments, only 3,000 (11%) evidenced a change in methylation state, but over 85% of changes involved a gain of a 5-methyl group on a CpG site (net increase in methyation). The ability to score CpG sites as partially methylated among gDNA copies in a sample opens up a new avenue for assessing DNA methylation responses to changing environments. By quantitatively distinguishing a ``mixed'' population of copies of one CpG site, we can begin to identify dynamic, non-binary, continuous-response reactions in DNA methylation intensity or density that previously may have been overlooked as noise.